2015
DOI: 10.1038/sc.2014.238
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic spinal cord lesions are influenced by the degree of cervical spine involvement in multiple sclerosis

Abstract: Study design: Cross-sectional analyses. Objective: To determine whether cervical spinal cord lesions predict the presence of thoracic cord lesions in multiple sclerosis (MS) patients. Setting: Single MS Clinic, AZ, USA. Methods: All MS patients, with MRI studies of the brain, cervical and thoracic spine obtained during a single scanning session, were acquired during a 1-year period. Clinical, demographic and imaging covariates were used in a multivariate regression model to refine predictors of thoracic cord i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 20 publications
4
24
0
Order By: Relevance
“…There are scant published data about craniocaudal location of myelitis and pain. We suggest that one reason NMOSD TM sufferers experience more pain than MS patients might relate to the differing proportions of cervical and thoracic cord involvement in the two conditions 4. In support of this hypothesis, Okuda et al 5 have reported that pain in MS associates with upper/mid-thoracic damage and propose an autonomic aetiology.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…There are scant published data about craniocaudal location of myelitis and pain. We suggest that one reason NMOSD TM sufferers experience more pain than MS patients might relate to the differing proportions of cervical and thoracic cord involvement in the two conditions 4. In support of this hypothesis, Okuda et al 5 have reported that pain in MS associates with upper/mid-thoracic damage and propose an autonomic aetiology.…”
Section: Discussionmentioning
confidence: 59%
“…Known differences in NMOSD and MS cord lesions potentially provide insights into this disparity and the observation that MS lesions predominantly involve the cervical cord, whereas NMOSD lesions are frequently thoracic4 might be a contributor, particularly as a recent paper implicated thoracic cord lesions in the aetiology of MS chronic pain 5…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, magnetic resonance imaging (MRI) of the spinal cord in MS patients demonstrated a higher frequency of cervical spinal cord lesions than thoracic or lumbar spinal cord lesions (32, 33). Recent advanced MRI imaging has pointed to a predominance of lesions in the cervical spinal cord of MS patients probably due to the fact that the cervical spinal cord has a greater cross-sectional area and contains more myelin per spinal segment than lower segments of the spinal cord (34). This study highlighted the importance of including imaging of different segments of the spinal cord in MS patients to improve understanding of disease progression and to facilitate treatment choices (34).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advanced MRI imaging has pointed to a predominance of lesions in the cervical spinal cord of MS patients probably due to the fact that the cervical spinal cord has a greater cross-sectional area and contains more myelin per spinal segment than lower segments of the spinal cord (34). This study highlighted the importance of including imaging of different segments of the spinal cord in MS patients to improve understanding of disease progression and to facilitate treatment choices (34). Neuroanatomical differences of the cervical versus thoracic or lumbar spinal cord may extend to differences in angioarchitecture and thus hemodynamic parameters, which will finally impact on immune cell trafficking to the different segments of the spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) of the brain and spinal cord is the method of choice for in vivo assessment of MS‐related brain and spinal cord pathology . However, lesion location and load within the CNS correlate poorly with clinical disability and have limited prognostic value …”
Section: Introductionmentioning
confidence: 99%